2012
DOI: 10.1038/sc.2012.161
|View full text |Cite
|
Sign up to set email alerts
|

Systemic hypothermia in acute cervical spinal cord injury: a case-controlled study

Abstract: Introduction: Systemic hypothermia remains a promising neuroprotective strategy. There has been recent interest in its use in patients with spinal cord injury (SCI). In this article, we describe our extended single center experience using intravascular hypothermia for the treatment of cervical SCI. Methods: Thirty-five acute cervical SCI patients received modest (33 1C) intravascular hypothermia for 48 h. Neurological outcome was assessed by the International Standards for Neurological Classification of Spinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(77 citation statements)
references
References 22 publications
0
76
0
1
Order By: Relevance
“…There has, over the years, been modest interest in therapeutic hypothermia for traumatic SCI, 27 with interest more recently focusing on systemic cooling. 12,26 Hypothermia has been shown to have beneficial effects in trauma as diverse as reducing tissue metabolic demand, decreasing hemorrhage and edema formation, moderating apoptosis and excitotoxicity, reducing glial cell activation, decreasing the strength of the inflammatory response, and preserving blood vessel and blood-brain barrier structure. 53,62 Much modern research focuses on the therapeutic potential of mild systemic hypothermia (that is, a body temperature of 32°-35°C).…”
Section: Discussionmentioning
confidence: 99%
“…There has, over the years, been modest interest in therapeutic hypothermia for traumatic SCI, 27 with interest more recently focusing on systemic cooling. 12,26 Hypothermia has been shown to have beneficial effects in trauma as diverse as reducing tissue metabolic demand, decreasing hemorrhage and edema formation, moderating apoptosis and excitotoxicity, reducing glial cell activation, decreasing the strength of the inflammatory response, and preserving blood vessel and blood-brain barrier structure. 53,62 Much modern research focuses on the therapeutic potential of mild systemic hypothermia (that is, a body temperature of 32°-35°C).…”
Section: Discussionmentioning
confidence: 99%
“…Of the research studies completed, a total of 5 were retrieved (Table 1): 1 prospective case series, 4 1 combined prospective and retrospective study, 22 2 retrospective case series of the same patient population in a phase 1 feasibility study reviewing complications 19 then outcomes after 1 year, 20 and 1 case report.…”
Section: Resultsmentioning
confidence: 99%
“…21 Levi et al 19,20 used an Alsius CoolGard catheter in the femoral vein starting at postinjury hour 9.17 (SD, 2.24 hours) for a total of 47.6 hours (SD, 3.1 hours). Dididze et al 22 also used an Alsius CoolGard catheter initiated at postinjury hour 7.76 (SD, 1.09 hours) for 46.77 hours (SD, 1.71 hours). Hansebout and Hansebout 4 used a spinal cord cooling saddle and initiated cooling at 7.1 hours (mean) for 3.7 hours (mean).…”
Section: Initiation Method and Duration Of Coolingmentioning
confidence: 99%
See 1 more Smart Citation
“…Holzer et al reported that therapeutic mild hypothermia (target temperature, 32°C to 34°C) increased the rate of a favorable neurologic outcome and reduced mortality in patients successfully resuscitated after cardiac arrest due to ventricular fibrillation [33]. The neurological outcome of patients with acute cervical spinal cord injury was improved by receiving modest (33°C) intravascular hypothermia for 48 h [34]. Moreover, local deep cooling (dural temperature 6°C) could improve the neurological outcome of patients with a neurologically complete spinal cord injury [35].…”
Section: Hypothermia Treatmentmentioning
confidence: 98%